2016
DOI: 10.1080/15476286.2016.1236172
|View full text |Cite
|
Sign up to set email alerts
|

Toward the promise of microRNAs – Enhancing reproducibility and rigor in microRNA research

Abstract: The fields of applied and translational microRNA research have exploded in recent years as microRNAs have been implicated across a spectrum of diseases. MicroRNA biomarkers, microRNA therapeutics, microRNA regulation of cellular physiology and even xenomiRs have stimulated great interest, which have brought many researchers into the field. Despite many successes in determining general mechanisms of microRNA generation and function, the application of microRNAs in translational areas has not had as much success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
130
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(134 citation statements)
references
References 123 publications
2
130
0
2
Order By: Relevance
“…These observations, along with the conservation of microRNAs and their targets in species that can be part of the human food supply (Friedman et al., ; Lee et al., ; van Herwijnen et al., ) sparked the interest for dietary microRNAs’ (sometimes termed as xenomiRs) transfer and function in human consumers (Auerbach et al., ; Fabris & Calin, ; Kang et al., ; Witwer, ; Witwer & Halushka, ; Witwer & Hirschi, ; Witwer, McAlexander, Queen, & Adams, ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
“…These observations, along with the conservation of microRNAs and their targets in species that can be part of the human food supply (Friedman et al., ; Lee et al., ; van Herwijnen et al., ) sparked the interest for dietary microRNAs’ (sometimes termed as xenomiRs) transfer and function in human consumers (Auerbach et al., ; Fabris & Calin, ; Kang et al., ; Witwer, ; Witwer & Halushka, ; Witwer & Hirschi, ; Witwer, McAlexander, Queen, & Adams, ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
“…Proper validation of hybridization, amplification and interpretation is required [95]. While a full discussion of the unique challenges of miRNA research is beyond the scope of this paper, we direct the reader to the excellent article by Witwer and Halushka for further discussion [95]. …”
Section: Discussionmentioning
confidence: 99%
“…Notably, there are nuances to transfecting or introducing miRNAs or their inhibitors into cells. The supraphysiologic overexpression of miRNAs obtained by transfection may have different biologic effects [95]. Mayya et al have shown that miRNAs work in a variable dose-dependent fashion with their mRNA binding sites [96].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, microRNAs have been useful in diagnoses of bladder, kidney, prostate and testicular cancers [8,10]. There are still challenges for microRNAs in its applications, as it can be difficult to assay for miRNA and miRNAs may affect multiple genes that are not of interest [11].…”
Section: Introductionmentioning
confidence: 99%